What do families value most about the care home where their older adult relatives live? - Leché-Martín, Eduardo Alberto; Saz-Gil, María Isabel; Gil-Lacruz, Ana Isabel; Sierra-Berdejo, María José; Gil-Lacruz, Marta (Frontiers in Public Health, 2024)
The 2030 Agenda and the principles of Corporate Social Responsibility (CSR) define companies and public authorities as agents for social change sharing objectives such as promotion of health, personal development and social engagement, among others.Care homes for the elderly are an example of organisations that should be particularly aware of these priorities. Since they work with vulnerable groups, collaboration with the families is essential in ensuring residents' well-being.The objective of this study is to analyse the factors that condition the satisfaction of relatives of residents in a care home for the elderly located in a rural environment in the province of Huesca (Spain).The 51 relatives interviewed rated the following points very positively: location and accessibility, food service, medical resources, communication with the staff and management team. A high percentage, however, did not know about the channels for volunteer work and institutional involvement. Some psychosocial indicators related to families' interaction and communication with the staff and their potential involvement in the dynamics of the institution have considerable weight in how they explain their satisfaction.